THE EXPRESSION OF COMMUNICATIVE STRATEGIES THROUGH POLITENESS AND CULTURAL CODES IN UZBEK SOCIAL DISCOURSE - Baymuradova Laylo Qaxramonovna (Sciental Journals Publishing, 2025)
This article analyzes the expression of politeness norms and cultural codes in Uzbek social discourse and their role in communicative strategies. The results show that cultural codes and etiquette norms play a crucial role in forming effective persuasive and social adaptation strategies in communication processes. The study employs a pragmalinguistic approach to examine how cultural context influences communicative effectiveness.
Keywords: Politeness norms, cultural codes, communicative strategies, social discourse.